PIDANA MATI SEBAGAI ULTIMUM REMEDIUM TERHADAP PELAKU TINDAK PIDANA KORUPSI DANA BANTUAN SOSIAL COVID-19 (Faculty of Law, University of Palembang, 2023)
Law no. 31 of 1999 in conjunction with Law no. 20 of 2001 confirms the rules regarding the death penalty in Article 2 paragraph (2), namely